Role of Oral and Topical Nasal Steroids in Prevention of Ethmoidal Nasal Polyp Recurrence after Intranasal Polypectomy: A Comparative Study of 64 Cases (Medical Forum Monthly, 2024)
Objective: To study the effect of oral and intranasal topical corticosteroids on nasal polyp recurrence after intranasal polypectomy.Study Design: Perspective, comparative.Place and Duration of Study: This study was conducted out in ENT and Head & Neck Surgery Department, Bolan Medical Complex Hospital, Quetta, from March 2010 to March 2013.Materials and Methods: Sixty four patients of both sexes with diagnosis of ethmoidal nasal polyp underwent intranasal polypectomy. Then patients were divided into two groups, Group-A and Group-B. There were 32 patients in each group. In group-A the patients received oral and intranasal topical steroids postoperatively while in group-B patients did not receive oral and intranasal topical steroids. Both groups were followed-up for any recurrence of polyps at interval of 3, 6 and 12 months.Results: Recurrence rates in group-A were 6.25%, 12.5% and 21.87%, while the recurrence rates in group-B were 12.5%, 28.12% and 43.75% at interval of 3, 6 and12 months.Conclusion: A postoperative short course of oral steroids followed by topical nasal steroid spray after intranasal polypectomy can reduce the recurrence rate of ethmoidal nasal polyps significantly.